Kinetics of Circulating Progenitor Cells and Chemotactic Factors in Full-Term Neonates with Encephalopathy: Indications of Participation in the Endogenous Regenerative Process - Nikolaos Efstathiou; Georgios Koliakos; Katerina Kantziou; Georgios Kyriazis; Aristeidis Slavakis; Vasiliki Drossou; Vasiliki Soubasi (Biomolecules)
Preclinical studies have shown that progenitor cells (PCs) are mobilized toward injured tissues to ameliorate damage and contribute to regeneration. The exogenous therapeutic administration of PCs in children affected by neonatal encephalopathy (NE) is a promising, yet underreported, topic. In this prospective study, we investigated whether endogenous circulating progenitor cells (CPCs) are involved in intrinsic regeneration mechanisms following neonatal brain injury. Thirteen full-term infants with moderate/severe NE, eleven with perinatal stress, and twelve controls were enrolled. Blood samples were collected on days 1, 3, 9, 18, and 45, as well as at 8 and 24 months of life, and were analyzed with a focus on Endothelial Progenitor Cells, Haematopoietic Stem Cells, and Very Small Embryonic-Like Stem Cells, in addition to chemotactic factors (erythropoietin, IGF-1, and SDF-1). Correlations between CPCs, chemotactic factors, and brain injury were assessed using serum levels of brain injury biomarkers (S100B and neuron-specific enolase), brain MRIs, and Bayley III developmental scores. Increased brain injury biomarkers were followed by the upregulation of SDF-1 receptor and erythropoietin and, finally, by elevated CPCs. These findings suggest a potential endogenous regenerative effort, primarily observed in the moderate encephalopathy group, but this is suppressed in cases of severe brain injury. Mimicking and enhancing endogenous regeneration pathways in cases of failure—regarding cell type and timeframe—could provide a novel therapeutic model.